2020
DOI: 10.1111/ajr.12645
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner perceptions of the health of Australian First Nations' Peoples: Preliminary findings

Abstract: Objective To probe health practitioner perceptions of Australian First Nations' Peoples' health and to compare these with reported burden of disease, social determinants and culturally safe health systems data. Design An online survey tool was used to collect self‐reported responses from health practitioners to answer literature‐derived questions regarding underlying issues in Australian First Nations' Peoples' health. Setting Responses to the survey were sought from rural and urban health service locations ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, recent research into health system cultural awareness has found that the perceptions of health professionals on the key issues impacting Aboriginal and Torres Strait Islander health were significantly misaligned with the documented burden of preventable disease in these communities. The study found a need to place greater emphasis on the expansion of the Aboriginal and Torres Strait Islander health workforce and on the inclusion of pre- and in-service training of all health professionals in culturally safe health systems and practice and in Indigenous health and burden of disease subject areas ( Crouch et al , 2020 ). In the current study context, these findings together suggest that exercise physiologist/physical fitness industry workforce perceptions may impact exercise participation by Aboriginal and Torres Strait Islander Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent research into health system cultural awareness has found that the perceptions of health professionals on the key issues impacting Aboriginal and Torres Strait Islander health were significantly misaligned with the documented burden of preventable disease in these communities. The study found a need to place greater emphasis on the expansion of the Aboriginal and Torres Strait Islander health workforce and on the inclusion of pre- and in-service training of all health professionals in culturally safe health systems and practice and in Indigenous health and burden of disease subject areas ( Crouch et al , 2020 ). In the current study context, these findings together suggest that exercise physiologist/physical fitness industry workforce perceptions may impact exercise participation by Aboriginal and Torres Strait Islander Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to the influence of negative historical and social experiences since the time of colonisation [ 7 ]. There is an extensive literature- and evidence-base on factors and conditions contributing to the health and wellbeing of Aboriginal and Torres Strait Islander peoples, including national burden-of-disease [ 8 ] and health determinants data [ 9 , 10 , 11 ]. Analyses of these data highlight opportunities for strengthening the duration and quality of life of Aboriginal and Torres Strait Islander people by addressing the causes of avertible morbidity and premature mortality [ 12 ].…”
Section: Introductionmentioning
confidence: 99%